Identifying the Speech Production Stages in Early and Late Adulthood by Using Electroencephalography - den Hollander, Jakolien; Jonkers, Roel; Mariën, Peter; Bastiaanse, Roelien (Frontiers in Human Neuroscience, 2019)
Structural changes in the brain take place throughout one’s life. Changes related to cognitive decline may delay the stages of the speech production process in the aging brain. For example, semantic memory decline and poor inhibition may delay the retrieval of a concept from the mental lexicon. Electroencephalography (EEG) is a valuable method for identifying the timing of speech production stages. So far, studies using EEG mainly focused on a particular speech production stage in a particular group of subjects. Differences between subject groups and between methodologies have complicated identifying time windows of the speech production stages. For the current study, the speech production stages lemma retrieval, lexeme retrieval, phonological encoding and phonetic encoding were tracked using 64-channels-EEG in 20 younger adults and 20 older adults. Picture-naming tasks were used to identify lemma retrieval and lexeme retrieval, . Nonword reading was used to target phonological encoding and phonetic encoding. Stimulus-locked and response-locked cluster-based permutation analyses were used to identify the timing of these stages in the full time-course of speech production from stimulus presentation until 100 ms before response onset in both subject groups. It was found that the timing of each speech production stage could be identified. Even though the older adults showed longer response times for every task, only the timing of the lexeme retrieval stage was later for the older adults compared to the younger adults, while no such delay was found for the timing of the other stages. The results of a second cluster-based permutation analysis indicated that clusters that were observed in the timing of the stages for one group were absent in the other subject group, which was mainly the case in stimulus-locked time windows. A z-score mapping analysis was used to compare the scalp distributions related to the stages between the older and younger adults. No differences between both groups were observed with respect to scalp distributions, suggesting that the same groups of neurons are involved in the four stages, regardless of the adults’ age, even though the timing of the individual stages is different in both groups.